SPECIFIC ASPECTS OF THE IMPLEMENTATION OF THE PRINCIPLES OF CRIMINAL PROCEDURE AT THE PREJUDICIAL LEVEL AND AT THE COURT LEVEL (World Bulletin of Management and Law, 2024)
In the article, following the principles of the criminal procedure and its specific features in the process of reviewing criminal cases before and after the trial, also, in the process of pre-trial investigation, rapid search, inquiry, preliminary investigation and trial, issues related to the importance of the principles of criminal procedure in protecting the rights and legal interests of the participants in the process were scientifically analyzed and appropriate proposals were put forward in this regard.
Keywords: principle; process; legal norms; law